Morphine-induced internalization of the L83I mutant of the rat μ-opioid receptor - Cooke, A E (Br J Pharmacol, 2015)
BACKGROUND AND PURPOSE: Naturally occurring single-nucleotide polymorphisms (SNPs) within GPCRs can result in alterations in various pharmacological parameters. Understanding the regulation and function of endocytic trafficking of the μ-opioid receptor (MOP receptor) is of great importance given its implication in the development of opioid tolerance. This study has compared the agonist-dependent trafficking and signalling of L83I, the rat orthologue of a naturally occurring variant of the MOP receptor. EXPERIMENTAL APPROACH: Cell surface elisa, confocal microscopy and immunoprecipitation assays were used to characterize the trafficking properties of the MOP-L83I variant in comparison with the wild-type receptor in HEK 293 cells. Functional assays were used to compare the ability of the L83I variant to signal to several downstream pathways. KEY RESULTS: Morphine-induced internalization of the L83I MOP receptor was markedly increased in comparison with the wild-type receptor. The altered trafficking of this variant was found to be specific to morphine and was both G-protein receptor kinase- and dynamin-dependent. The enhanced internalization of L83I variant in response to morphine was not due to increased phosphorylation of serine 375, arrestin association or an increased ability to signal. CONCLUSIONS AND IMPLICATIONS: These results suggest that morphine promotes a specific conformation of the L83I variant that makes it more liable to internalize in response to morphine, unlike the wild-type receptor that undergoes significantly less morphine-stimulated internalization, providing an example of a ligand-selective biased receptor. The presence of this SNP within an individual may consequently affect the development of tolerance and analgesic responses. LINKED ARTICLES: This article is part of a themed section on Opioids: New Pathways to Functional Selectivity. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2015.172.issue-2